Influence of Heat Treatments on the Mechanical Properties of Ultrasonic Welded AA 2024/CF‐PA66‐Joints*. Issue 9 (18th December 2012) - Balle, Frank; Huxhold, Stefan; Emrich, Stefan; Wagner, Guntram; Kopnarski, Michael; Eifler, Dietmar
<x xml:space="preserve">Abstract</x> The ultrasonic welding technology is well suited to realize hybrid joints of aluminum alloys and carbon fiber reinforced polymers (CFRP). Hybrid Al/CFRP‐joints by using self‐hardening aluminum alloy like AA 1050 or AA 5754 were already realized. To achieve ultrasonic welded Al/CFRP‐joints with enhanced joint strengths, the application of a heat treatable aluminum alloy was realized. The precipitation hardening of aluminum alloys like AA 2024 allows new process steps during the ultrasonic welding of these materials with CFRP to improve the joint strength. In this study, the influence of different heat treatments on mechanical properties and microstructure of ultrasonic welded AA 2024/CF‐PA66‐joints will be described. A distinction was made between pre‐weld and post‐weld heat treatments. The pre‐weld heat treatment of the metallic sheets was a solution annealing at a temperature of T = 500 °C followed by water quenching and immediate welding with CFRP. In case of the post‐weld heat treatment the entire ultrasonical welded AA 2024/CF‐PA66‐joints were heat treated with two different procedures: artificial aging for 20 h at a temperature of T = 180 °C or natural aging for 1 week at ambient temperature.